2018
DOI: 10.3390/nu10101426
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role for Osteocalcin in the Development of Atherosclerosis and Blood Vessel Disease

Abstract: There is increasing evidence for the involvement of the skeleton in the regulation of atherosclerotic vascular disease. Osteocalcin, an osteoblast derived protein, exists in two forms, carboxylated and undercarboxylated osteocalcin. Undercarboxylated osteocalcin has been linked to the regulation of metabolic functions, including glucose and lipid metabolism. Features of atherosclerosis have been associated with circulating osteocalcin; however, this association is often conflicting and unclear. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 94 publications
(120 reference statements)
4
44
1
3
Order By: Relevance
“…Some studies have demonstrated an inverse relationship between osteocalcin level and arterial calcification (carotid or coronary atherosclerosis) [16]. However, despite the seemingly favorable metabolic and cardiovascular effects associated with osteocalcin, it is also implicated in the pathogenesis of vascular calcification, which occurs in the chronic stage of atherosclerosis [17]. In bone formation, γ-carboxylated osteocalcin has been determined to bind to calcium and hydroxyapatite as part of bone mineralization [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated an inverse relationship between osteocalcin level and arterial calcification (carotid or coronary atherosclerosis) [16]. However, despite the seemingly favorable metabolic and cardiovascular effects associated with osteocalcin, it is also implicated in the pathogenesis of vascular calcification, which occurs in the chronic stage of atherosclerosis [17]. In bone formation, γ-carboxylated osteocalcin has been determined to bind to calcium and hydroxyapatite as part of bone mineralization [17].…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin is a pleiotropic protein regulating glucose and lipid metabolism, nitric oxide release, and endothelial homeostasis depending on its carboxylation status [30]. Opposite to PTH, an association of serum osteocalcin with cardiovascular death is unclear, being U-shaped as well as gender-and age-dependent [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Этому спо собствует ряд факторов инициации и прогрессирования атеросклероза: дислипидемия, активация маркеров оксидативного стресса (С-реактивный белок), системы интерлейкинов и факторов роста, что, в свою очередь, приводит к эндотелиальной дисфункции, локальному повышению концентрации металлопротеиназ, запуску системы RANK/RANKL/остеопротегерин и выделению ряда катепсинов с формированием участков коллагеновых волокон как центров будущей кальцификации в проекции атеросклеротической бляшки. Предполагается, что это и есть общие механизмы кальцификации аорты и коронарных артерий, а также нарушения минеральной плотности костной ткани [50].…”
Section: Fundamental and Practical Aspects Of Coronary Artery Calcifiunclassified